Standardisation of hybrid seed production technology of first Indian mustard (Brassica juncea) hybrid NRCHB 506 - Maity, Aniruddha; Chakravarty, S K; Yadav, J B (The Indian Journal of Agricultural Sciences, 2012)
Field experiments were conducted in 2009–10 and 2010–11 to standardise the sowing time and planting ratio of the parental lines of the recently released Indian mustard (Brassica juncea L. Czern. & Coss) hybrid NRCHB 506. The results indicated that the optimum sowing time of parental lines of NRCHB 506 is the third week of October to achieve higher yield of good quality hybrid seed. Optimum planting ratio of female to male parental line for hybrid seed production was 8:2. Further increase in number of female rows per male row decreased the plant and plot yield of the hybrid seed production plot. The results pertaining to flowering phenology and characters, seed yield and its attributing traits indicated that delay in sowing beyond October reduces the value of those characters significantly leading to decline in seed yield from seed parent. The primary factor responsible for the reduction of values in the late sowing was the higher temperature during reproductive and seed feeling stage. Sowing in October and growing of plants in relatively high temperature extended the vegetative phase, i e delayed the flowering by four days as compared to that in November sowing which experienced a lower temperature during early growth stage. Delay in sowing reduced the flowering duration which had a direct impact on the number of flowers, siliqua set, seeds/siliqua and finally seed yield/plant.